A molecular dynamics study of melting and dissociation of tungsten nanoparticles - Li, Min; Wang, Jun; Fu, Baoqin; Hou, Qing (AIP advances, 2015)
Molecular dynamics simulations were conducted to study the melting and dissociation of free tungsten nanoparticles. For the various interatomic potentials applied, the melting points of the tungsten nanoparticles increased with increasing nanoparticle diameter. Combining these results with the melting point of bulk tungsten in the experiment, the melting point of nanoparticles with diameters ranging from 4 to 12 nm could be determined. As the temperature increases, free nanoparticles are subject to dissociation phenomena. The dissociation rate was observed to follow Arrhenius behavior, and the Meyer–Neldel rule was obeyed. These results are useful in understanding the behavior of tungsten dust generated in nuclear fusion devices as well as for the preparation, formation, and application of tungsten powders.